Reformasi Birokrasi dalam Pelayanan Publik Melalui Aplikasi Halodoc di Kota Mataram - Azizatul Farhaini; Bayu Karunia Putra; Dinatul Aini (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Digitization is a process of social engagement based on an increase in computer assistance, new media, and communication platforms for the economy, society and culture (digitalization). Due to the existence of digitalization, every use of technology through the intermediary of digital devices continues to transform all forms of activities that are directly related to the government administration process which has the aim of increasing effectiveness, efficiency, and creating quality services. So, through this mechanism of information and communication technology, it has had such a big impact in the joints of life today. Thus, one manifestation in the context of bureaucratic reform, especially in the process of providing public services, must provide improvements in the service process that are faster, easier, and of higher quality. However, the reality of providing a service, especially related to health services, is still not running according to community expectations, because it is proven in health services which are still sometimes crowded, queued, and convoluted. The purpose of this study is to find out how effective and efficient the application of this Halodoc application is, especially among the community. The research method used is a literature study method, where sources and data are obtained directly through journals, books, and other written sources. The results of this study related to